KONSEP MONTESSORI TENTANG PENDIDIKAN ANAK USIA DINI DALAM PERSPEKTIF PENDIDIKAN ISLAM - Indah Fajarwati (Jurnal Pendidikan Agama Islam, 2014)
Education is the business of adults to prepare children to be able to live independently and is able to perform the duties of his life as well as possible. The toddler years are a golden period for the growth and development of children. Development of each child must be observed, education and teaching needs to be ailored to the child’s development. Montessori is early childhood education leaders who opened the eyes of their sensitive period in children, Montessori asserted that education is self-education. Montessori then use the freedom and liveliness of the child with the best in the method, so that each child had the opportunity to evolve according to the nature and talent. In Islam, God entrusted the child is to be protected and educated with the best. Therefore, addressing the development and early childhood education, the need for an educational program that is designed in accordance with the child’s developmental level. This study aims to describe and analyze the Montessori concept of early childhood education in the perspective of Islamic education. Data collection through literature study is based on primary and secondary data. Data analysis using analytic descriptive with inductive thinking patterns. The results showed: 1) Montesssori shift from teacher-education center central (teachers as a source of learning) be child-central (protégé as a center of learning); 2) Sensitive Periods expressed early age is a sensitive period; 3) The freedom and independence according to the Montessori system is not real freedom, but freedom is limited; 4) Child’s Self-Construction stating that children construct their own development of his soul; 5) At the time of early childhood have a soul absorbent range of knowledge and experience in his life. Montessori concept in Islamic educational perspective, the emphasis is on the child’s intellectual is right. However, it should pay attention to other aspects such as emotional aspects and skills.